Occupational acute pesticide poisoning: a cross-sectional study of Turkish vegetable and fruit farmers based on self-reported symptoms and job characteristics - Cevik, Celalettin; Ozdemir, Raziye; Ari, Sezgin (La Medicina del Lavoro, 2020)
Background: Occupational pesticide poisoning is an important public health concern worldwide, especially in developing countries. Objectives: This study was aimed at determining the prevalence and risk factors of acute pesticide poisoning (APP) among the vegetable and fruit farmers in Karacabey District in northwest Turkey. Methods: The study group consisted of 565 farmers. The dependent variable of the study is APP defined according to the World Health Organization’s APP case definition matrix. The study’s independent variables are the farmers’ sociodemographic characteristics and the preventive measures they use when they are applying pesticides. The chi-square and logistic regression analysis analyzed the relationship between the dependent and independent variables. Results: A total of 64 (11.3%) farmers reported APP and 75% of them presented to a health institution due to symptoms. The factors associated with increased risk of APP were: illiteracy (odds ratio (OR)=2.5), 14 years and less farming experience (OR=3.3), not reading the pesticide labels (OR=6.4), and contact with liquid pesticides (OR=2.3). Conclusions: The study shows that approximately one out of ten farmers experience APP. Training programs should be planned and monitored to improve farmers’ awareness of the dangers of pesticides, and they should be encouraged to adopt and implement protective measures.